2010
DOI: 10.1016/j.neuropsychologia.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Callosal degradation in HIV-1 infection predicts hierarchical perception: A DTI study

Abstract: HIV-1 infection affects white matter circuits linking frontal, parietal, and subcortical regions that subserve visuospatial attention processes. Normal perception requires the integration of details, preferentially processed in the left hemisphere, and the global composition of an object or scene, preferentially processed in the right hemisphere. We tested whether HIV-related callosal white matter degradation contributes to disruption of selective lateralized visuospatial and attention processes. A hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 96 publications
5
29
1
Order By: Relevance
“…Our results contribute to a growing body of research demonstrating that HIV is associated with compromised white matter integrity throughout the brain (Bing et al , 2001; Chang et al , 2008; Chen et al , 2009; Du et al , 2012; Hoare et al , 2011; Müller-Oehring et al , 2010; Pfefferbaum et al , 2009; Pomara et al , 2001; Thurnher et al , 2005; Wright et al , 2015; Wu et al , 2006; Zhu et al , 2013). Specifically, HIV was associated with widespread decreases in FA, but more regionally specific increases in MD within the corpus callosum and thalamus.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our results contribute to a growing body of research demonstrating that HIV is associated with compromised white matter integrity throughout the brain (Bing et al , 2001; Chang et al , 2008; Chen et al , 2009; Du et al , 2012; Hoare et al , 2011; Müller-Oehring et al , 2010; Pfefferbaum et al , 2009; Pomara et al , 2001; Thurnher et al , 2005; Wright et al , 2015; Wu et al , 2006; Zhu et al , 2013). Specifically, HIV was associated with widespread decreases in FA, but more regionally specific increases in MD within the corpus callosum and thalamus.…”
Section: Discussionsupporting
confidence: 54%
“…The majority reported significantly reduced FA and/or elevated MD among HIV-infected compared to HIV-uninfected persons in the corpus callosum (Chang et al , 2008; Chen et al , 2009; Du et al , 2012; Hoare et al , 2011; Müller-Oehring et al , 2010; Pfefferbaum et al , 2009; Thurnher et al , 2005; Wang et al , 2016; Wright et al , 2015; Wu et al , 2006; Zhu et al , 2013). This is likely symptomatic of a general decline in white matter integrity, as FA reduction and/or MD elevation among HIV-infected persons have also been reported in several other regions, including the cingulate cortex, frontal, parietal, temporal, and occipital white matter (Chang et al , 2008; Chen et al , 2009; Pomara et al , 2001; Zhu et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The current study found an association between global facilitation and higher white matter integrity in the genu, anterior body, and the splenium of the CC. However, the current sample of pediatric-onset MS patients showed the same degree of compromise in both anterior (genu) and posterior (splenium) callosal regions, whereas the HIV-1 group showed greater compromise in the posterior callosal regions than in the anterior regions (Müller-Oehring et al, 2010). Thus, it was not possible in the current study to determine whether facilitation effects were more strongly associated with compromise in the posterior regions as has been previously suggested (Müller-Oehring et al, 2010).…”
contrasting
confidence: 45%
“…Notably, white matter abnormalities are prevalent and the degree of neurocognitive impairment has been correlated with the amount of damage (15, 16). Imaging studies have also revealed cortical myelin disruption, volume loss, and diminished structural integrity of the corpus callosum in HAND patients, which were even more pronounced in cART-treated individuals (1719).…”
Section: Introductionmentioning
confidence: 99%